DEIKSIS PERSONA BAHASA LAMAHOLOT DIALEK LAMAHOLOT TENGAH - Swalar, Thomas Krispianus (MAJU : Indonesian Journal of Community Empowerment, 2024)
Indonesian people in their daily interactions generally use regional languages, while Indonesian is used by a small portion of the population. Each regional language is used by the community according to its function. The most important function is as a means of communication between members of the community. In Indonesia, the government is obliged to protect, maintain and preserve every regional language because the regional languages ​​in Indonesia have their own uniqueness which lies not only in their language structure but also in the cultural values ​​behind that structure. This uniqueness is a cultural wealth that is maintained as an effective potential for the development of regional languages ​​which leads to the development of national culture. The aim of this research is to examine the forms of BL Deixis of the Central Lamaholot Dialect and to examine and explain the use of BL Persona Deixis of the Central Lamaholot Dialect